(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Coal is one of the huge consumed fossil fuels and has huge energy demands in various energy sectors especially in power generation sector and in industries. Coal is a common energy source in the cement and steel industry and in coming years India will rely heavily on the utilization of fossil fuels for its huge energy demands. As India is targeting to attain zero-carbon emission till 2070, there is pressing demand on efficient utilization of fossil fuels so as to minimize any harm to our ecosystem. In this paper we have performed thermal and chemical analysis on the quality of coal so as to determine the best quality of coal which can be utilized properly as well as graded for appropriate usage in various energy demanding sectors. We provided stage process test technique procedures for proximate analysis, ultimate analysis, mineral matter, physical and thermal characteristics, and so on. After having detailed analysis of coal samples, it is found that by increasing Sulfur content in coal, consumption of coal can be decreased significantly which will ultimately decrease the air pollution and less coal will be consumed in cement production.